The Influence of Service Quality on Customer Loyalty with Customer Satisfaction as a Mediation Variable and Customer Perceived Value as a Moderation Variable - Ria Atmaja, Dodi; Razelina , Vanesa (Journal of Business and Behavioural Entrepreneurship, 2025)
This research aims to assess how service quality influences customer satisfaction, loyalty and repurchase intentions on the Shopee e-commerce application in Indonesia. Shopee as one of the largest e-commerce platforms in the country has millions of users with various experiences regarding its services. The method used in this research is quantitative by collecting data through questionnaires distributed to Shopee users. The data obtained was then analyzed using SEM to determine the relationship between the variables studied. The findings from this research show that service quality has a positive and significant effect on customer satisfaction, which then has a positive impact on loyalty and repurchase intentions. This research provides important insights for Shopee management to continue to improve service quality to increase customer satisfaction, loyalty and repurchase intentions. Additionally, companies need to understand how customers assess the benefits and costs associated with using the Shopee application to design effective strategies to increase customer perceived value and ensure long-term business sustainability.